The tRNA-Derived Small RNAs Regulate Gene Expression through Triggering Sequence-Specific Degradation of Target Transcripts in the Oomycete Pathogen Phytophthora sojae - Wang, Qinhu; Li, Tingting; Xu, Ke; Zhang, Wei; Wang, Xiaolong; Quan, Junli; Jin, Weibo; Zhang, Meixiang; Fan, Guangjin; Wang, Ming-Bo; Shan, Weixing (Frontiers in Plant Science, 2016)
Along with the well-studied microRNA (miRNA) and small interfering RNA (siRNA) is a new class of transfer RNA-derived small RNA (tsRNA), which has recently been detected in multiple organisms and is implicated in gene regulation. However, while miRNAs and siRNAs are known to repress gene expression through sequence-specific RNA cleavage or translational repression, how tsRNAs regulate gene expression remains unclear. Here we report the identification and functional characterization of tsRNAs in the oomycete pathogen Phytophthora sojae. We show that multiple tRNAs are processed into abundant tsRNAs, which accumulate in a similar developmental stage-specific manner and are negatively correlated with the expression of predicted target genes. Degradome sequencing and 5′ RLM RACE experiments indicate tsRNAs can trigger degradation of target transcripts. Transient expression assays using GUS sensor constructs confirmed the requirement of sequence complementarity in tsRNA-mediated RNA degradation in P. sojae. Our results show that the tsRNA are a class of functional endogenous sRNAs and suggest that tsRNA regulate gene expression through inducing sequence-specific degradation of target RNAs in oomycetes.